Development of microspheres for biomedical applications: a review - Hossain, Kazi M. Zakir; Patel, Uresha; Ahmed, Ifty (Springer, 2015)
An overview of microspheres manufactured for use in biomedical applications based on recent literature is presented in this review. Different types of glasses (i.e. silicate, borate, and phosphates), ceramics and polymer-based microspheres (both natural and synthetic) in the form of porous , non-porous and hollow structures that are either already in use or are currently being investigated within the biomedical area are discussed. The advantages of using microspheres in applications such as drug delivery, bone tissue engineering and regeneration, absorption and desorption of substances, kinetic release of the loaded drug components are also presented. This review also reports on the preparation and characterisation methodologies used for the manufacture of these microspheres. Finally, a brief summary of the existing challenges associated with processing these microspheres which requires further research and development are presented.